Origins, development and abandonment of an Iron Age village : further archaeological investigations for the Daventry International Rail Freight Terminal, Crick & Kilsby, Northamptonshire 1993-2013 - Chapman, Andy, 1951- (DIRFT ;, 2015)
This volume is the second of two reports on archaeological excavations undertaken ahead of the eastern expansion of Daventry International Rail Freight Terminal (DIRFT) which lies in the northern watershed region of Northamptonshire at its border with Warwickshire.